Gasoline prices and economic policy uncertainty: what causes what, and why does it matter? Evidence from 18 selected countries - Olanipekun, Ifedolapo; Olasehinde-Williams, Godwin; Akadiri, Seyi Saint (Springer Heidelberg, 2019)
In this paper, we examine asymmetric causal relationships between gasoline prices and economic policy uncertainty in a panel of 18 countries over the period 1998-2017, using the recently introduced panel causality approach of Hatemi et al (Appl Econ, 48:2301-2308, 2016) that accounts for asymmetric dynamics and is robust to both cross-sectional dependence and slope heterogeneity. Empirical findings reveal asymmetric causal relationships between gasoline prices and economic policy uncertainty in the sampled countries. Specifically, results show that economic policy uncertainty and gasoline prices have positive and negative asymmetric bidirectional causal relations in 13 countries. No feedback causality was detected between gasoline prices and economic policy uncertainty in 5 countries. Based on the results, we infer that positive and negative asymmetric causal relations exist between economic policy uncertainty and gasoline price, with attendant policy implications in sampled regions.
Keywords: Economic policy uncertainty; Gasoline prices; Asymmetry; Panel approach